2020
DOI: 10.1136/bmjopen-2020-037643
|View full text |Cite
|
Sign up to set email alerts
|

Identifying optimal frameworks to implement or evaluate digital health interventions: a scoping review protocol

Abstract: IntroductionDigital health interventions (DHIs) are defined as health services delivered electronically through formal or informal care. DHIs can range from electronic medical records used by providers to mobile health apps used by consumers. DHIs involve complex interactions between user, technology and the healthcare team, posing challenges for implementation and evaluation. Theoretical or interpretive frameworks are crucial in providing researchers guidance and clarity on implementation or evaluation approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Therefore, this may limit definitive conclusions if results present a high risk of bias or are not applicable outside their local context, limiting the wider clinical relevance. Second, there is currently no ‘gold-standard’ framework to evaluate the implementation of DHIs, 27 likely leading to heterogenous measures reported. In order to facilitate meaningful comparison between studies, the WHO evaluation framework for monitoring and evaluating DHIs 20 has been used as the basis for this review due to its applicability across different income settings and healthcare contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this may limit definitive conclusions if results present a high risk of bias or are not applicable outside their local context, limiting the wider clinical relevance. Second, there is currently no ‘gold-standard’ framework to evaluate the implementation of DHIs, 27 likely leading to heterogenous measures reported. In order to facilitate meaningful comparison between studies, the WHO evaluation framework for monitoring and evaluating DHIs 20 has been used as the basis for this review due to its applicability across different income settings and healthcare contexts.…”
Section: Discussionmentioning
confidence: 99%
“…DHIs can be defined as "health services delivered electronically through formal or informal care. DHIs can range from electronic medical records used by providers to mobile health (mHealth) apps used by consumers" [2]. The World Health Organization has recently produced a classification of DHIs, identifying four main types: clients, health care providers, health systems, and data services [3].…”
Section: Digital Health Interventionsmentioning
confidence: 99%
“…A recent scoping review of KT highlighted a range of theories, models and frameworks but reported that there was still little evidence of use in practice [ 26 ]. How frameworks can be utilised within the digital health context is also an area of interest [ 27 ] as is the need to engage with end-users to develop actionable plans and outcomes [ 28 ]. Huzair et al [ 29 ] argue that KT is not just about recognising that stakeholders have “a diverse set of understandings, values and goals, but are influenced by their socio-political and economic environment.” They recommend using a range of inter-disciplinary research methods and approaches to understand better the environment in which knowledge is intended to be used, including undertaking interviews with, and observing a wide range of relevant stakeholders.…”
Section: Developing An Engagement Frameworkmentioning
confidence: 99%